2016
DOI: 10.14260/jemds/2016/979
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Comparing Stenting Versus Non-Stenting After Uncomplicated Ureteroscopy for Ureteric Stones

Abstract: The placement of stents has been a standard practice since 1967. The advantage of routine stenting is that it minimizes postoperative ureteral obstruction and renal colic that may result from ureteral oedema caused by balloon dilatation or stone manipulation. There are various disadvantages resulting from it including flank pain, voiding symptoms, infections, stent related stone formation and encrustation. Various studies recommend them to be used only for procedures with complications such as ureteric injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Another study of 20 patients with DJ stent and the reported complications stated 90% positive results with one or more than one reported stent related Lower urinary tract symptoms 23 . A study reported pain after SWL stent placement in 44% of patients along with dysuria, urgency and increased use of analgesia, which was subsided after stent removal 24 . A DJ stent, which was forgotten for four years in 40 years old female showed sepsis in ER, the severely encrusted DJ stent was then removed, and patient get symptom free 25 responsible to cause severe morbidity in pediatric population along with UTI, hematuria and encrustation of stent resulting in obstruction 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study of 20 patients with DJ stent and the reported complications stated 90% positive results with one or more than one reported stent related Lower urinary tract symptoms 23 . A study reported pain after SWL stent placement in 44% of patients along with dysuria, urgency and increased use of analgesia, which was subsided after stent removal 24 . A DJ stent, which was forgotten for four years in 40 years old female showed sepsis in ER, the severely encrusted DJ stent was then removed, and patient get symptom free 25 responsible to cause severe morbidity in pediatric population along with UTI, hematuria and encrustation of stent resulting in obstruction 26 .…”
Section: Discussionmentioning
confidence: 99%